The Analysis of Student’s Interest in Reading English Text Books at SMP Negeri 27 Manokwari - Alfons Napoleon Arsai; Maria Putri Narwadan; Almendita F. W Arsai (Universitas Muhammadiyah Enrekang, 2024)
The objective of this scholarly investigation is to discern the extent of eighth-grade students' engrossment with English textbooks at SMPN 27 Manokwari. The researchers employed a sophisticated research design by implementing a combination of quantitative and qualitative methodologies. The quantitative approach facilitated the systematic tabulation of data into numerical formats, while the qualitative methodology served to articulate and expound upon data devoid of numerical parameters. The participants in this erudite exploration comprised 20 eighth-grade students enrolled at SMPN 27 Manokwari, with the data collection tools encompassing meticulously crafted questionnaires and insightful interviews. Through meticulous data analysis, the research findings unveiled a noteworthy elevation in the students' ardor for perusing English textbooks, categorizing their interest as notably elevated. The diligent endeavors undertaken by the students in assimilating the contents of English textbooks encompassed practices such as preliminary readings before scheduled lessons, dedicated perusal within the precincts of the library, in-depth examination within the confines of their homes, and the proactive measure of seeking elucidation from the instructor when faced with incomprehensible subject matter. This intricate exploration not only gauged the students' proclivity for English textbook engagement but also illuminated the multifaceted strategies employed by them to fortify their understanding of the material at hand.